2006
DOI: 10.1093/ije/dyl213
|View full text |Cite
|
Sign up to set email alerts
|

Is tuberculin skin testing useful to diagnose latent tuberculosis in BCG-vaccinated children?

Abstract: TST results helped identify children in a BCG-vaccinated population who had recent exposure to persons with pulmonary tuberculosis, were probably infected with M. tuberculosis, and could benefit from treatment for their latent tuberculosis infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
3
12
0
4
Order By: Relevance
“…Analyses using different results combination allowed us to show consistency of the association. Odds ratio was found to be higher when a more specific combination was used (IGRA and TST positive compared with IGRA and TST negative results) [26].…”
Section: Discussionmentioning
confidence: 91%
“…Analyses using different results combination allowed us to show consistency of the association. Odds ratio was found to be higher when a more specific combination was used (IGRA and TST positive compared with IGRA and TST negative results) [26].…”
Section: Discussionmentioning
confidence: 91%
“…16 Figure 1 identify children in a BCG-vaccinated population who had recent exposure to persons with pulmonary TB, and were probably infected with M. tuberculosis. 20 We considered the Mantoux test to be positive for subjects. A study in Hamburg, Germany compared a Mycobacterium tuberculosis-specific enzyme-linked immunospot (ELISPOT) assay to the tuberculin test.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Silva VMC [22] et al and Srour-Fihmi S et al [23] in age groups ranging from 20 years to over 60 years have shown that being BCG vaccinated had no effect on the booster response. Studies also show that the effect of BCG is insignificant when TST reactions are ≥ 10mm [5,6,18,24–26]. …”
Section: Discussionmentioning
confidence: 99%